Assessing the Potential Causal Relationship between Polycystic Ovary Syndrome and Post-Traumatic Stress Disorder: A Bidirectional Mendelian Randomization Study - Xian Zhang; Jie Song; Bin Liu; Minchen Dai; Binxiang Wang; Xiaowei Cai; Yifan Hu; Yingying Mao; Fan Qu (Clinical and Experimental Obstetrics & Gynecology)
Background: Observational studies have reported that individuals diagnosed with polycystic ovary syndrome (PCOS) face a heightened vulnerability to developing post-traumatic stress disorder (PTSD). However, it is unclear whether this relationship is causal. Consequently, we implemented a bidirectional Mendelian randomization (MR) analysis to examine the empirical causal association of PCOS and PTSD. Methods: We acquired genetic association data for PCOS through a comprehensive meta-analysis from several large-scale genome-wide association studies (GWASs), which enrolled 10,074 cases and 103,164 controls. For PTSD, we obtained data from a GWAS performed by the Psychiatric Genomics Consortium Posttraumatic Stress Disorder (PGC-PTSD) group. The study included a total of 23,212 cases of PTSD and 151,447 controls of European ancestry. For both PCOS and PTSD, we carefully selected genetic instruments that met the rigorous significance threshold (p < 5 × 10-8, r2 < 0.01). To investigate the causal association between PCOS and PTSD, we conducted bidirectional Mendelian randomization (MR) analyses. The primary analysis employed the inverse-variance weighted (IVW) method, complemented by alternative MR approaches such as the maximum-likelihood method, MR-Egger regression, Mendelian randomization-Robust Adjusted Profile Score (MR-RAPS), and MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO) test. Sensitivity analyses were also carried out to verify the robustness of this association. Results: In this study, we identified and utilized 14 genetic variants as instruments for PCOS, while 2 genetic variants were selected as instruments for PTSD. Our findings demonstrated that a genetic predisposition to PCOS was significantly associated with an elevated risk of developing PTSD (odds ratio (OR) = 1.11, 95% confidence interval (CI): 1.03–1.19, p = 7.27 × 10-3 for IVW). MR-Egger regression analysis was performed, and the results did not provide evidence of directional pleiotropy (p intercept = 0.187). Sensitivity analyses utilizing alternative MR methods consistently yielded similar results, supporting the robustness of our findings. Furthermore, in the reverse MR analysis, we observed no significant association between genetic predisposition to PTSD and the risk of developing PCOS (OR = 1.15, 95% CI: 0.69–1.91, p = 0.586 for IVW). Comparable null associations were also observed when alternative MR methods were employed. Conclusions: Through a genetic epidemiological approach, we found that genetic predisposition to PCOS was associated with an increased risk of PTSD, suggesting a potential causal relationship between PCOS and PTSD. Nonetheless, further investigation is necessary to elucidate the underlying mechanism through which PCOS contributes to the development of PTSD.